Immunogenicity of a recombinant fusion construct composed of intrinsically unstructured, low polymorphic segments derived from merozoite surface protein 2 and trophozoite exported protein 1. Issue 36 (23rd August 2019) - Tiendrebeogo, Regis Wendpayangde; Spallek, Ralf; Oehlmann, Wulf; Singh, Mahavir; Theisen, Michael; Nebie, Issa; Moret, Remy; Roussilhon, Christian; Corradin, Giampietro
Abstract: To overcome the extensive polymorphism found in human Plasmodium antigens and to avoid the lengthy characterization of their 3 dimensional structure and subsequent production of the native proteins we have been concentrated in large unstructured, non-or low-polymorphic fragments present in the blood stage of P. falciparum . Three fragments derived from the 2 family-specific and constant regions of merozoite surface protein (MSP2) and PFF0165c protein were previously selected for evaluation as potential single vaccine candidates. In order to increase and optimize their potential efficacy against P. falciparum infection the 3 antigens were combined in a single DNA recombinant product (FusN) and compared its antigenicity with that of single antigens in sera of volunteers living in endemic countries. Immunogenicity of the FusN was then compared with that of the mixture of 3 antigens in 3 strains of mice. Antigen specific, affinity purified human antibodies were then tested in antibody dependent cellular inhibition and merozoite opsonization assays. In addition, the antigen specific antibody response and its association with protection from malaria infection were determined. The data collected indicate that the recombinant product is an equal or better antigen /immunogen than fragments used either alone or as a mixture for vaccination in combination with adjuvant. In addition, antibody response to FusN shows a stronger association with protection than single fragments. The use of a single construct as vaccine would drastically reduce the cost of manufacturing and development of the GMP product.